The Relationship Between Corporate Social Responsibility (CSR) and Malaysia Halal Industry - Abdul Rahim, Mohd Rafiq (‘Abqari Journal, 2020)
The Malaysia halal industry is growing, and a lot of interventions have been taken by the government to grow the industry. Halal certified status carry a very strong obligation towards Muslim community. However, some food and products businesses were caught with unethical and irresponsible act due to multiple cases related to halal food and products indirectly impacted Muslim consumers at large. The study is a desk and descriptive research. It is based on secondary data. Author reviewed the existing literatures such as journals, magazines and research works related to the conceptual of Corporate Social Responsibility (CSR) and halal industry. The analysis has shown food manufacturer need to undertake a serious move to review company procedures in dealing with halal issues to engage in productive and legitimate operations. Therefore, this paper elaborates the halal concept from the lens of various scholars and its relationship to the Corporate Social Responsibility (CSR) and business ethics related to halal industry.